Spìrnì problemi neosudnostì u krimìnal′nomu pravì Ukraїni - Burdìn, Volodimir Mikolajovič (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The problem of soundness and unsoundness of mind is related to many factors which may influence an individual’s psyche and, consequently, his or her ability to control his or her behaviour. It is through this multiplicity of factors influencing the psychological conduct that we should analyse the problem of criminal liability of people who committed socially dangerous acts in a state that made it impossible for them to control their behaviour, if they found themselves in this state of their own will. In the article, the author analyses in particular the significance, from the point of view of criminal law, of a situation in which individuals voluntarily bring themselves to a state in which they become unable to control their own behaviour.
Keywords: Ukraina; prawo karne; niepoczytalność